Can agility training affect athletic power performance? - Igor Jukić; Goran Sporiš; Luka Milanović; Daniel Bok; Daniel Bok (Exercise and Quality of Life)
Propose of this study was to determine effects of agility training on athletic power performance. Eighty healthy college-age men (age 19 ± 1.1 years; body mass 77.2 ± 7.1 kg; height 180.1 ± 7.1 cm; body fat percentage 10.8 6 1.6) participated in this study. Subjects were assigned randomly to 2 experimental groups (EG) and 1 control group (CG). The EG groups were required to perform 3 sessions per week on alternate days (i.e., on Monday, Wednesday, and Friday) for 10 weeks. There were no statistical significant differences between CG and EG in initial measurement, also there were no differences found between CG in initial and final measurement. The main result of this study is associated with the aglity training–induced changes in athletic power performance.